The Effect Of Training and Communication Skills On Employee Work Productivity In The Operational Department Of The Zhm Premiere Hotel Padang - Defa Yuanda; Feri Ferdian (CV Putra Publisher, 2026)
This study analyzes how training programs and communication competencies shape the work productivity of operational staff at The ZHM Premiere Hotel Padang. Despite being recognized as critical drivers of hotel service performance, the simultaneous role of both variables among operational personnel has received limited scholarly attention. A quantitative causal-associative design was employed, with all 89 operational employees serving as the study sample through total sampling. Data were gathered via Likert-scale questionnaires and analyzed using SEM-PLS through SmartPLS 4 software. Descriptive results placed training (M = 4.53), communication skills (M = 4.58), and work productivity (M = 4.51) in the